PENGEMBANGAN LKS UNTUK MEMFASILITASI PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI ALJABAR - Vitantri, Ciptianingsari Ayu; 'Ulya, Himmatul; Jayus, Jayus; Sholihah, Mashfiyatus (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
The objectives of this study are to describe and create Student Worksheets based on Concept Mapping that are valid, effective, and practical to facilitate students' understanding of mathematical concepts. This research uses the Plomp research and development model that has been modified by Romadhan into 4 phases namely 1) initial investigation, 2) design, 3 ) realization, 4) tests, evaluations and revisions. The LKS was tested on a limited basis to three students of class VII A and field trials on 24 students of class VII D MTs Plus Darul Ulum. Data collection was performed using worksheet validation sheets, student response sheets, teacher response sheets, and concept understanding sheets. The results showed that the Student Worksheet (LKS) based on concept mapping to facilitate students' understanding of mathematical concepts had fulfilled valid, effective, and practical criteria. Based on the results of the validity percentage 80% and 78.13%. The results of the effectiveness based on student's responses in the questionnaire and result tests of conceptual understanding. Student worksheet effective is responses of students who meet both criteria with score Sf= 73,9% and test understanding of the concept which meets both criteria with score Sa= 80,29%. Practicability test on the student worksheet based on questionnaire responses of the teacher which meet both criteria whit score Sp= 76%. Proposition for further development, student worksheets should be developed in other topics of mathematics.Keywords: student worksheet, concept mapping, understanding of concept mathematical, algebra.